Small Medium Enterprises Transforming to Digital given E-Commerce Users' Intention to Shop Online - Ari Apriani; Siti Annisa Wahdiniawati (Dinasti International Journal of Management Science, 2023)
The aim of this study is to explore the digital transformation of SMEs concerning the intention to make online purchases, with the anticipated outcome being the formulation of effective strategies for SMEs to boost consumer inclination towards online shopping. The study involved consumers using Shopee and Tokopedia in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas, with a sample size of 220 respondents spread across Jabodetabek. Data collection utilized a questionnaire method where respondents provided answers in a choice-based format, employing a Likert scale for question scaling. Quantitative analysis, specifically using SEM analysis tools, was the method employed in this research. The findings highlighted that perceived usefulness and trust significantly and positively influenced attitudes towards online shopping and the intention to purchase online. Additionally, perceived ease of use had a positive and significant effect on attitudes towards online shopping, yet it did not directly impact the intention to buy online. This research's implications offer valuable insights into digital transformation, aiming to enhance SMEs and alter consumer shopping behaviors in the digital era.